PROSES LAHIRNYA HAK CIPTA TERHADAP PEMBUATAN VIDEO KLIP BERDASARKAN UNDANG – UNDANG NOMOR 19 TAHUN 2002 - Adi Sanjaya, I Dewa Gede; Palguna, I Dewa Gede (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 11, November 2013, 2013)
This paper entitled "The Birth Process of Copyright to the Making of Video Clip Based on Regulation Number 19 of 2002". The method used in making this journal is to analyze the normative juridical cases and regulations that are interrelated. In the making of this video clip is not simple because it requires a cost and Human Resources. That Human Resources are the Artist, Director, and Producer. That three part have a crucial position in the manufacture of a Video Clips, so The Writer made this paper to find out who is the holder and process of copyright to the Video Clip if examined from the Regulation Number 19 of 2002 about Copyright. Explication of the legal status and the process of the copyright to the video clip is very important to know in order to avoid conflict between parties who’s involved in the process of making the Video Clip.
Keywords: Copyright, Legal Status, Video Clip